Sumerian grammar - Edzard, Dietz Otto. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2003)
It seems safe to say that this Sumerian Grammar by Professor D.O. Edzard will become the new classic reference in the field. It is an up-to-date, reliable guide to the language of the Sumerians, the inventors of cuneiform writing in the late 4th millennium B.C., and thus essential contributors to the high cultural standard of the whole of Mesopotamia and beyond. Following traditional lines, the Grammar describes general characteristics, origins, linguistic environment, phonetics and phonology, morphology, syntax, and phraseology. Due attention is given to the symbiosis with Semitic Akkadian, with which Sumerian was to form a veritable linguistic area. With lucid explanations of all technical linguistic theory. Each transliteration carries its English translation.